Effects of sports participation on psychological stress in female students in region 3 of Kermanshah - Feyzkhademi, Ali; Hajipoor, Saadat; Azimi, Shahram; Hosseini, Mehrdad Jalalian (Marsland Press, 2010)
The aim of this study was to investigate the effects of sports participation on the psychological stress levels of female students 15-18 years old. Psychological stress is defined as a collection of nonspecific reactions against organisms in reflections and exposure to any factor that should be faced. Stress control includes several factors, and, in particular, sports participation is thought to be effective. This quasi-experimental research was performed using pre-test plan–test, after-test, and control groups. Research subjects for the control group were 30 people chosen randomly. The subjects of stress were tested by a 40-item stress questionnaire and then tested in step independent variable “Sports participation” included volleyball education and skills training for three months and three weekly sessions of 75-90 minutes. This was carried out to investigate its effect on the dependent variable "stress." We did not observe any statistically meaningful difference between the mean scores of stress-control group and experiment group scores at pre-test in p<0.05; however, statistically meaningful differences were observed between the mean scores of stress control group and experiment group scores on the post test stage (p<0.05) and between the mean scores of stress in the control group pre-test and post-test in (p<0.05). In addition, A statistically meaningful difference was observed statistically meaningful differences were observed between the mean scores of stress in the experiment group pre-test and post-test (p<0.05).